A new experimental and theoretical investigation on the structures of aminoethyl phosphonic acid in aqueous medium based on the vibrational spectra and DFT calculations - Roldan, María L. (2013)
A new study on the structural and vibrational properties of the aminoethylphosphonic acid was performed in aqueous solution phase by using the self-consistent reaction field (SCRF) method. We have studied and characterized it by infrared and Raman spectroscopies in solid and aqueous solution phases. The Density Functional Theory (DFT) method with Pople’s basis set show that three stable zwitterions for the title molecule have been theoretically determined in aqueous solution and that probably they are present in it medium. Here, the solvent effects were studied by means of the self-consistent reaction field (SCRF) method with the polarized continuum model (PCM). The harmonic vibrational frequencies for the optimized geometries of the three zwitterions were calculated at the B3LYP/6-31G∗ level of the theory. A complete assignment of the IR and Raman spectra of the compound in aqueous solution was performed combining the DFT calculations with Pulay’s Scaled Quantum Mechanics Force Field (SQMFF) methodology in order to fit the theoretical frequency values to the experimental ones. Moreover, Natural Bond Orbital (NBO) and topological properties calculations were performed to analyze the energies and geometrical parameters of its three zwitterions in aqueous medium as well as the magnitude of the intramolecular interactions. The bond orders, atomic charges, solvation energies, dipole moments, molecular electrostatic potentials and force constants parameters calculated for zwitterions in aqueous solution, may be used to gain chemical and vibrational insights into related compounds.